STRATEGI KOMUNIKASI CORPORATE IDENTITY BPJS KETENAGAKERJAAN MELALUI MEDIA DIGITAL - Anna Farianingrum; Shinta Prastyanti; Bekti Istiyanto; Toto Sugito; Agoeng Noegroho (Kinesik, 2023)
COVID-19 pandemic occurred in December 2019 hit almost all countries, causing many companies to terminate their employment, and resulting in high unemployment including Banyumas. This resulted in an increase in workers submitting Old Age Security claims to meet the needs of life. The surge in JHT claims and the implementation of PPKM is a challenge for BPJS Ketenagakerjaan as a public service institution to overcome problems and determine strategies for company sustainability, for this reason, Lapak Asik (Service Without Physical Contact) was created, namely a digital application as a means of submitting JHT claims. This study aims to analyze the corporate identity strategy of Employment BPJS in managing digital media and its role in service. The theory used is corporate identity and computer mediated communication. The research method uses a descriptive qualitative approach. Data collection through interviews, observation, and documentation. The results showed that the Purwokerto Employment BPJS had not optimally implemented corporate identity (behavior) indicators while the computer-mediated communication component had been implemented properly.